2022
DOI: 10.3390/min12080977
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Theoretical, Observational, and Modeled Deformation of Ground Subsidence: The Case of the Alhada Pb-Zn Mine

Abstract: In this study, the probability integral method, Synthetic Aperture Radar Interferometry (InSAR), and the Okada dislocation model were collaboratively used to analyze deformation in the Alhada Pb-Zn mine. The predicted deformation values of the subsidence centers in three subsidence areas were 107 mm, 120 mm, and 83 mm, respectively, as predicted using the probability integral method. The coherent scatterer InSAR technique was used to analyze the time-series deformation of the mining area, and the same subsiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Figure 3 depicts the distribution of PS output results along with their corresponding PS points. For the purpose of ensuring the accuracy of monitoring results, numerous scholars [12,27,30,44,45,[53][54][55][56][57] have conducted comparisons between monitoring results and leveling measurement values, GPS, GNSS, D-InSAR, and SBAS-InSAR monitoring values, to validate their precision. If the disparities between these two sets of results are minimal and essentially consistent, it can be inferred that the monitoring is feasible.…”
Section: Verification Of Ps-insar Monitoring Results Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 depicts the distribution of PS output results along with their corresponding PS points. For the purpose of ensuring the accuracy of monitoring results, numerous scholars [12,27,30,44,45,[53][54][55][56][57] have conducted comparisons between monitoring results and leveling measurement values, GPS, GNSS, D-InSAR, and SBAS-InSAR monitoring values, to validate their precision. If the disparities between these two sets of results are minimal and essentially consistent, it can be inferred that the monitoring is feasible.…”
Section: Verification Of Ps-insar Monitoring Results Accuracymentioning
confidence: 99%
“…Although these methods offer high accuracy monitoring levels, they are limited in terms of comprehensively monitoring point quantity and fail to depict subsidence characteristics within mining areas. With the continuous advancement of remote sensing technology, novel approaches such as Unmanned Aerial Vehicle (UAV) photogrammetry, Light Detection And Ranging (LiDAR), and Interferometric Synthetic Aperture Radar (InSAR) technologies have emerged for surface deformation monitoring [12][13][14][15][16][17]. InSAR technology possesses numerous advantages, including all-weather capability, highprecision measurements, cost-effectiveness, and wide monitoring coverage.…”
Section: Introductionmentioning
confidence: 99%
“…As the exploitation map is unknown, we used a horizontal rectangular sill with uniform opening to simulate surface deformation, equivalent to the total mining impact. Specifically, according to the dislocation theory in the halfspace, the surface displacement field caused by the opening component can be expressed as follows [29]:…”
Section: Deformation Modeling Based On Rectangular Modelmentioning
confidence: 99%
“…These InSAR-based deformation measurements can also be used to probe the geometry and process of mining activities. He et al (2022) used the multi-source Okada model, a dislocation model for shear and tensile fault motions in an elastic half-space [29], to simulate ground deformation obtained using the coherent scatterer InSAR technique. The results showed that the predicted and observed deformations were highly correlated, with an overall misfit of less than 5 cm [30].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Chen [7] ,Liu [8] ,Wang [9] ,He [10] , and Feng [11] have demonstrated the efficacy of PS-InSAR in diverse applications, ranging from mining subsidence detection to landslide monitoring and seismic event analysis. These studies showcase the versatility of PS-InSAR in capturing spatial and temporal variations in surface deformation, providing a foundation for our exploration in the unique setting of the Bortala Mongol Autonomous Prefecture.…”
Section: Introductionmentioning
confidence: 99%